도로터널 방재시설의 소방관계법령 개선방안 - 서효선(Hyo-Seon Seo); 황영권(Young-Kwon Whang); 이승철(Seung-Chul Lee) (한국화재소방학회 논문지, 2019)
When a fire occurs in a road tunnel, it is likely to develop into a major disaster because of its sealed structural characteristics. Because of this, a range of disaster prevention facilities should be installed, and they should show their appropriate functions in fire prevention and response. In addition, the installation of essential disaster prevention facilities is missing due to the lack of considering an extension of continuous tunnels and soundproof tunnels. For these reasons, it was judged that an amendment to the law would be necessary. Therefore, this paper reviewed the changes in domestic laws related to the disaster prevention facilities of road tunnels, and the results of the study on the parts that need to be revised in the fire-related laws through a comparative analysis between laws are as follows. First, consecutive tunnels should consider the sum of the extensions of the individual tunnels and ensure that the soundproof tunnels are included in the category of tunnels in the law. In this way, the necessary disaster prevention facilities should be installed. Second, it is necessary to secure a legal justification for installing disaster prevention facilities in tunnels. Therefore, it is essential that water mist fire extinguishing system facilities, emergency broadcasting facilities, and leading lights, which are excluded from installation in tunnels, are specified in the Fire-related laws. Third, to specify in the law that air respirators must be provided in the tunnel is necessary from the viewpoint of the field response. Accordingly, it will make a great contribution to the fire-fighting activities and the life-saving efforts by fire-fighters. 도로터널에서 화재가 발생하면 밀폐된 구조적 특성상 대형재난으로 발전할 가능성이 높기 때문에 각종 방재시설이 잘 설치되어 화재예방과 대응에 제 기능을 발휘해야 한다. 연속터널의 연장 및 방음터널을 고려하지 않아 필수 방재시설의 설치가 누락되어 법령의 개정이 필요한 것으로 판단된다. 이에 따라 본 논문에서 도로터널의 방재시설과 관련한 국내 법령들의 변천사항을 검토하고, 각 법령 간 비교분석을 통해 소방관계법령에서 개정이 필요한 부분을 연구한 결과는 다음과 같다. 첫째, 연속터널은 개별터널의 연장의 합을 고려하도록 하고 방음터널이 터널의 범주에 포함되도록 하여 필수 방재시설이 설치가 되지 않는 일이 없도록 해야 한다. 둘째, 터널 내 방재시설 설치의 법적 당위성 확보가 필요하므로 터널에 설치가 제외된 시설인 미분무소화설비, 비상방송설비, 유도등이 법령에 명시될 필요가 있다. 셋째, 현장대응의 입장에서 터널 내에 공기호흡기를 비치하도록 명시하여 소방대원들의 진압활동 및 인명구조에 크게 기여할 수 있도록 한다.